IMPATIENS MAMASENSIS (BALSAMINACEAE), A NEW SPECIES FROM WEST CELEBES, INDONESIA - UTAMI, NANDA; WIRIADINATA, HARRY (REINWARDTIA, 2010)
UTAMI, N & WIRIADINATA H, 2010. Impatiens mamasensis (Balsaminaceae), a new species from West Celebes, Indonesia. Reinwardtia 13(2): 211-212. - Impatiens mamasensis Utami & Wiriad. (Balsaminaceae) is described as a new species.